2015
DOI: 10.4238/2015.august.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of alterations to the transcriptome of Loquat (Eriobotrya japonica Lindl.) under low temperature stress via de novo sequencing

Abstract: ABSTRACT. Loquat (Eriobotrya japonica Lindl.), which originates from the cooler hill regions of southwestern China, is a typical subtropical evergreen tree. Loquat is one of the most important economic crops in China, but the available genomic information is very limited. Here, we present the first deep transcriptomic analysis of loquat. De novo assembly generated 116,723 contigs and 64,814 unigenes using Illumina sequencing technology. A total of 45,739 unigenes were annotated by Nr, GO, and COG datasets. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The rational classification of protein coding is critical to maximize the use of transcripts for functional research. The results of the COG analysis showed that the R function (general function prediction only) constituted the greatest proportion, followed by the K function (transcription), L function (replication, recombination and repair) and T function (signal transduction mechanisms),which was similar to the results reported by Gong [17]. This result indicated that the gene expression of loquat under low-temperature stress is related to the above functions and suggested that the use of transcriptome sequencing technology is an effective method for the study of functional genes.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…The rational classification of protein coding is critical to maximize the use of transcripts for functional research. The results of the COG analysis showed that the R function (general function prediction only) constituted the greatest proportion, followed by the K function (transcription), L function (replication, recombination and repair) and T function (signal transduction mechanisms),which was similar to the results reported by Gong [17]. This result indicated that the gene expression of loquat under low-temperature stress is related to the above functions and suggested that the use of transcriptome sequencing technology is an effective method for the study of functional genes.…”
Section: Plos Onesupporting
confidence: 87%
“…Current research on loquat has mainly focused on cell genetics [6,7], physiology and biochemistry [8,9], molecular markers [10], molecular clones [11,12], etc. Several transcriptome studies in loquat focused on flower bud differentiation [13], fruit development and ripening [14,15], and postharvest storage [16], research on transcriptome in cold stress of loquat is limited [17], little is known about its cold tolerance mechanisms. Previous studies have been performed using second generation sequencing technology, and many unigenes have been obtained, however, transcriptomic sequences using second generation sequencing technology may be misassembled without a high-quality genome sequence or full-length (FL) transcriptomic sequences available as a reference [18].…”
Section: Introductionmentioning
confidence: 99%
“…These unigenes were used for BLASTX-algorithm based searches and annotations against the protein databases Nr, SwissPort, COG, KEGG, and GO. In total, 24,911 unigenes (34.62%) were annotated in sugar apple, which is much smaller than other fruit trees, such as pineapple (58.33%), mango (85%), and loquat (70.57%), and similar to the number annotated in manchurian walnut (39.92%) and “Bartlett” pears (32.8%) (Gong et al, 2015; Nham et al, 2015; Sherman et al, 2015; Hu et al, 2016; Liu and Fan, 2016). This indicated that the functions of a large portion of the genes of sugar apple have not yet been identified.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, cold tolerance is an intricate biological process controlled by numerous factors. However, limited data were available regarding either physiological or genetic mechanisms that control the cold resistance ability of loquat, illustrating that the related regulatory mechanisms would accelerate cold-resistant breeding projects and enhance fruit production (Gong et al, 2015). Based on these, in this study, the physiological indices of different organs in loquat under cold stress were determined, and a comparative transcriptome analysis was performed against the rachis organs of two loquat varieties with distinct cold resistance to reveal the potential gene regulatory pathways, as well as the cross talk of genes controlling cold resistance in loquat.…”
Section: Discussionmentioning
confidence: 99%